Effect of grain size on the very high cycle fatigue behavior and notch sensitivity of titanium. (December 2019) - Sajadifar, S.V.; Wegener, T.; Yapici, G.G.; Niendorf, T.
Graphical abstract: Highlights: ECAE processing enhanced the very high cycle fatigue performance of grade 4 titanium at room temperature. Smoother geometries improved the fatigue performance of grade 4 titanium. UFG titanium showed a strong sensitivity to the sample geometry. UFG titanium was seen to be more prone to the intergranular fracture in very high cycle fatigue regime. Abstract: The very high-cycle fatigue performances of coarse-grained and ultrafine-grained titanium samples with different geometries at ambient temperature and various stress amplitudes were investigated. Severe plastic deformation improves monotonic strength of titanium at the cost of a loss in ductility. Ultrafine-grained titanium demonstrates a superior fatigue performance compared to that of coarse-grained counterparts in the high-cycle fatigue regime, however, suffers notch sensitivity. Furthermore, in the very high-cycle fatigue regime stress-life curves merge unexpectedly. Microstructural inhomogeneity in the ultrafine-grained titanium is expected to be the reason. Analysis of fracture surfaces reveals that the formation of fatigue slip marks is evident on the fatigued samples of both microstructural states. Ultrafine-grained titanium is more prone to the intergranular fracture.